Patriarchy in Maternal Society Belu Est Nusa Tenggara - Suar Adnyana, Ketu (e-Journal of Linguistics; Vol. 6. Juli 2012 No. 2, 2012)
This present study, which analyzed patriarchy in maternal society in Belu, is a qualitative one. Four couples were determined as informants. They were determined using snow ball sampling technique. The data were collected through non participatory observation and interview. The observation in the family domain was focused on the communication between the husbands and wives. What was observed was recorded in the field note book. What was observed was every speech event and the focus was the topic discussed, where and when the speech took place, and who took part in it. In addition, the researcher also recorded every speech event using a voice recorder, a handycamp and a camera. From the speech events observed, it was found that the men had superordinate position and the women had subordinate position. The dominating position could be observed from what linguistic strategies were used in communication. The men showed the power they had using instruction, interruption, and quiet strategy. The power the men had indicated that patriarchy was applied in the Belu maternal community. There were several similarities in regard to their speech behaviors between the maternal community and paternal   community.
Keywords: Patriarchy, maternal, speech strategies